The Effectiveness of Facebook Advertisements on Purchase Intention of Customers in Malaysia - Mahmud, Shah Roman Al (South Asian Journal of Social Sciences and Humanities, 2020)
The purpose of this empirical study is to examine the effectiveness of Facebook advertisement on enhancing consumer purchase intention. Facebook, as a social networking site, has become very popular among the people of all ages around the world. Facebook advertising is becoming very popular as it can reach to the mass people as a medium of social sites. The study is hopefully help Facebook stakeholder provide their customers with more customized messages and offer rewards and promotions to encourage them for exposing their products and services.